Efektivitas Aplikasi SIM Nasional Presisi (Sinar) dalam Perpanjangan Surat Izin Mengemudi di Satpas Polda Metro Jaya - Nurul Ma’rifah; Dini Gandini Purbaningrum (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study examines the effectiveness of the SIM Nasional Presisi (SINAR) application in facilitating the renewal of driver’s licenses at the Driver’s License Administration Unit (SATPAS SIM) of Polda Metro Jaya, DKI Jakarta. The SATPAS is responsible for managing and issuing driver’s licenses, and recent technological advancements have enabled a transformation of the renewal process from an in-person service to an entirely online platform via the SINAR application. This innovation eliminates the need for applicants to physically visit the SATPAS office, offering greater accessibility and efficiency. The research adopts a qualitative descriptive approach, with data gathered through observation, structured interviews with relevant stakeholders, and documentation analysis. Campbell’s (1989) Program Effectiveness Theory serves as the analytical framework, utilizing five evaluation indicators: (a) program success, (b) program target determination, (c) program satisfaction, (d) input and output levels, and (e) overall goal achievement. Findings reveal that the SINAR application effectively integrates the issuance and renewal processes by connecting directly to the Korlantas Polri SIM Data Center. This integration ensures seamless verification and processing of applications. The program has achieved its intended targets, particularly in meeting public needs for a fast, accurate, and convenient service. The shift to online renewals has significantly reduced processing time and logistical burdens for applicants, contributing to a notable increase in the number of SIM renewals in 2023 compared to previous years. Furthermore, user feedback indicates high satisfaction levels, largely due to the convenience of remote access, the clarity of procedural instructions, and the reliability of the application’s features. Despite minor technical challenges, the overall implementation of the online SIM renewal service at SATPAS Polda Metro Jaya is deemed highly effective.